Analysis of Risk Factors of Parenting Patterns using the Nurturing Care Framework Approach with the Incident of Stunting in Toddlers in a Case Study in the Working Area of Pagambiran Public Health Center - Amilia, Fenni; Masrul, Masrul; Yusrawati, Yusrawati; Lipoeto, Nur Indrawaty; Mariko, Rinang; Meinapuri, Malinda (Newinera Publisher, 2025)
Stunting is a linear growth disorder caused by malnutrition and recurrent infections. Prevention is through the Nurturing Care Framework (NCF) approach, which includes health care, adequate nutrition, responsive care, early learning opportunities, and safety and security. This study aims to analyze the relationship between NCF-based parenting risk factors and stunting among toddlers in the Pagambiran Padang Community Health Center (Puskesmas) work area. This study was analytical with a cross-sectional design, conducted from June 2024 to January 2025. Sampling used stratified random sampling and simple random sampling, totaling 214 toddlers aged 24-59 months. Data collection used a questionnaire and was analyzed using univariate, bivariate (chi-square), and multivariate (multiple logistic regression with the backward elimination method). The results showed a stunting prevalence of 43.9%. Parenting patterns using the NCF (composite) approach were less than good at 55.1%. Multivariate analysis showed that risk factors significantly associated with stunting were health care (p=0.011), adequate nutrition (p=0.000), and safety and security (p=0.023). Adequate nutrition was the dominant factor (OR=8.602). Meanwhile, early stimulation and responsive parenting did not show a significant relationship. The conclusion of this study is that there is a relationship between health care, adequate nutrition, and safety and security with stunting. Adequate nutrition is the dominant factor. Cross-sectoral collaboration is expected to address nutritional issues, provide basic health services, monitor growth and development, and implement a healthy environment based on the National Child Protection Framework (NCF).